Economic studies and management policies of Lirang Island, Southwest Moluccas, Indonesia - Femsy Kour (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2018)
In Lirang Islands border the fisherman was interact with Republic of Timor Leste Democratic because of difficult accessibility. Therefore, management and development of small islands were needed which fit with its potential, characteristic, and problems. The aim of this research were to analyze economic condition of Lirangs people using fishing rate analysis; to analyze policy of border and formalize the strategic of development Lirangs Island using public policy analysiss and SWOT Analysis. Commonly, Lirangs fisherman has fishing rate above 1 and it showed that they have well-being level to fulfill their need. A vew policies that support the development of Lirangs island as small island were: to improve their autonomy from fishing facilities and infrastructure (market, dock/jetty, base of landing base, ice factory, cold storage and water) and training for fisherman through founding, to improve their skills and control the technology; to improve the social and economic collaboration with Repubic of Timor Leste Democratic.